2014
DOI: 10.1111/ajag.12155
|View full text |Cite
|
Sign up to set email alerts
|

Community care for the Elderly: Needs and Service Use Study (CENSUS): Who receives home care packages and what are the outcomes?

Abstract: Being offered a home care package was not based on waiting time or unmet care needs. Reforms should include a transparent system of wait listing and prioritisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Access to healthcare is a fundamental social determinant of health that has been targeted by the World Health Organization to improve the availability and timeliness of quality healthcare [1]. Numerous studies have shown that timely and/or adequate access to healthcare promotes better health and well-being [2,3] and that inadequate access to care has been associated with greater psychological distress [4], lower levels of physical health [5], higher rates of rehospitalization [6], and overall higher risks of morbidity and mortality [3,7]. Moreover, a large body of literature has demonstrated the correlates and consequences of access to healthcare in a variety of settings and populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Access to healthcare is a fundamental social determinant of health that has been targeted by the World Health Organization to improve the availability and timeliness of quality healthcare [1]. Numerous studies have shown that timely and/or adequate access to healthcare promotes better health and well-being [2,3] and that inadequate access to care has been associated with greater psychological distress [4], lower levels of physical health [5], higher rates of rehospitalization [6], and overall higher risks of morbidity and mortality [3,7]. Moreover, a large body of literature has demonstrated the correlates and consequences of access to healthcare in a variety of settings and populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from fields of social geography, population geography, and gerontology carried out related studies. Studies have included topics such as spatial differentiation of aging [15][16][17], older people access to healthcare [18][19][20], and residential location and spatial behavior of the elderly [21][22][23][24]. The pattern and process of geographical things and their space-time characteristics are scale-dependent.…”
mentioning
confidence: 99%
“…Interestingly, Low et al . () have recently identified that there is some evidence that providers may be selecting clients easier to service rather than on the basis of need.…”
Section: Methodsmentioning
confidence: 99%
“…Existing industry regulation, culture and practice has supported an established service model in Australia that arguably makes translation of the objectives of CDC difficult. Interestingly, Low et al (2015) have recently identified that there is some evidence that providers may be selecting clients easier to service rather than on the basis of need.…”
Section: Methodsmentioning
confidence: 99%